Peran Profesionalisme Guru Dalam Meningkatkan Prestasi Belajar Siswa Di SDN 1 Batu Nampar - Suhaibatul Aslamiah (Al-Gafari : Manajemen dan Pendidikan, 2023)
Profession is something position work something professional relation with position or work certain ones with itself requires expertise, knowledge and skills certain too. In other words, work that is professional is only job made by special people prepare For That No job done by those who because No obtain work other. Study This aim For know How role and impact teacher professionalism increase performance Study students at SDN 1 Batu Nampar. Study This use study type qualitative with take location at SDN 1 Batu Nampar. Data collection using method observation, interview and documentation. Subject researcher in study This is head School, Class 5 Teacher, Class III Teacher, Class 2 Teacher, and School Operator. Data analysis techniques were carried out in a manner interactive and ongoing in a manner Keep going continuously until complete so that got to the point data saturation. Inspection data validation is carried out with data triangulation. Result of study This that the teacher's professional role for increase quality Study student especially in competence Teacher professionalism includes five aspects namely : 1) master material, structure, concept, and pattern think supporting science eye lessons taught , 2 ) master standard competency and competency base eye lessons taught, 3 ) develop material taught learning in a manner creative, 4) develop professionalism in a manner sustainable with do action reflective, and 5) make use of technology information and communication For develop self. Research in class V regarding impact teacher professionalism increase performance Study students at SDN 1 Batu Nampar so influential and every most of the year experience improvement. it can observed from results amount mark end of semester one year The last one is always increasing.